Proses Kreativitas Yus Wiradiredja dalam Mengaransemen Pupuh Magatru Raehan - Meta Liana; Setyo Yanuartuti; Indar Sabri (Syntax Corporation, 2023)
The creative process carried out by Yus Wiradiredja in arranging Pupuh Magatru to become Pupuh Magatru Raehan is a form of anticipation of an increasingly global era. Pupuh Raehan is the result of creativity that emerged as a response to increasingly global conditions. The influence of Western music can sometimes be found in various musical compositions that have been influenced by the process of globalization. Today, Western music has an almost equal influence in various countries around the world. Yus Wiradiredja arranged the Sundanese Pupuh Art to be more modern by adding western music idioms but not eliminating the Kasundaan elements in Raehan's Pupuh. This study aims to find out the meaning of Pupuh Raehan and to find out the creativity of Yus Wiradiredja in arranging magatru pupuhs. This study uses a descriptive qualitative method with non-interactive analysis techniques by examining documents and writings regarding Yus Wiradiredja's creativity in arranging Pupuh Magatru Raehan. Through this research it is known that Wiradiredja's creativity in processing pupuh art into dynamic and relevant performances is an inspiring example in facing the challenges of an ever-changing era.